Peningkatan Kompetensi Staf Pengajar Vokasi Melalui Pelatihan Intensif Perancangan Mesin Dengan Sistem CAD Model 3D - Naufal Aflah Hibatullah; Mochamad Iqbal Rokhim; Muhammad Khoirur Rijal; Slamet Raharjo; Muhammad Ihsan Al Qodar; Nor Fajri (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Competency in Computer-Aided Design (CAD) 3D–based design is a vital foundation in modern vocational engineering education. However, a major challenge in practice is the lack of uniform competency standards among teaching staff, where intuitive modeling practices are often found that are not fully defined, resulting in low design data integrity. This program aims to standardize such technical competencies through intensive training based on the Certified SolidWorks Associate (CSWA) curriculum. The program was conducted entirely in an offline setting over 65 instructional hours, covering fundamental topics ranging from design intent philosophy and parametric sketching to assembly validation using standard mates. The results demonstrate a perfect quantitative outcome, with 100% of participants successfully passing the examination and obtaining the international CSWA certification. This success indicates that structured training interventions are effective in equalizing participants’ competencies. The strategic implication of this program is the establishment of a uniform teaching standard among vocational lecturers, which ultimately ensures that graduates possess digital design literacy aligned with modern industrial best practices.